Public agricultural spending and growth in Ghana: Spending more, smarter - Aragie, Emerta A.; Artavia, Marco; Pauw, Karl (International Food Policy Research Institute, 2019)
In 2014, African heads of state reaffirmed their commitment to the Comprehensive African Agricultural Development Program (CAADP) through the adoption of the Malabo Declaration (AU 2014). The declaration included commitments to reduce hunger and poverty, boost intra-regional trade, enhance resilience to climate variability, and, in line with the Maputo Declaration a decade earlier, to continue allocating to agriculture at least 10 percent of government expenditure. Despite this long-standing spending commitment, Ghana’s agricultural budget share has remained well below 10 percent during the last decade. Depending on accounting principles followed, estimates range from 1 to 2 percent (CAGD 2016), 2 to 4 percent (FAO 2014) or 6 to 8 percent (MoFA 2017a). Given strong evidence that agricultural spending in developing countries yields significant returns (Mogues et al. 2015), Ghana’s relatively weak agricultural performance during the period from 2007 to 2017 may be linked to low levels of spending. At 4.3 percent per annum, agricultural GDP growth has only been half that realized in the non-agricultural sectors (MoF 2018). This weak agricultural growth has also not benefited the poor. Rural poverty has increased in recent years, especially in northern Ghana (GSS 2018). While budgetary allocations to agriculture matter, the quality of spending is as important (Akroyd and Smith 2007). In this regard, concerns have been raised about the decline in allocations to agricultural research, knowledge transfer, and infrastructure in favor of spending on routine operations (FAO 2014; World Bank 2017). Ideally, sector budgets should maintain a healthy balance between investments in a sector’s capacity to grow, e.g., infrastructure or farmers’ knowledge, and expenditures that are fully consumed in the same period, e.g., operational expenses or subsidies (Benin & Tiburcio 2018; Mogues et al. 2015). Following Ghana’s unfavorable assessment in the African Agricultural Transformation Scorecard (AATS), which was launched by the African Union (AU) in 2018, and in light of policy developments, budgetary trends, and socioeconomic outcomes, Ghana’s development partners called for an increase in funding allocated to the agriculture sector at the national Joint Sector Review for Agriculture in June 2019. They further called for improvements in the effectiveness of agricultural spending, with the distortionary effects of large-scale subsidy programs highlighted as a specific concern. A recent study led by IFPRI’s Ghana Strategy Support Program (GSSP) and FAO’s Monitoring and Analyzing Food and Agricultural Policies (MAFAP) project considers these issues further (Aragie et al. 2019). Specifically, using an economywide model of the Ghanaian economy, the research-ers examined how changes in the level and composition of public agricultural expenditure affect socioeconomic outcomes in the short and medium term in Ghana. This note highlights selected key study findings.